Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1986
DOI: 10.1108/eb002863
|View full text |Cite
|
Sign up to set email alerts
|

User‐Vendor Relationships in the Scottish Electronics Industry

Abstract: User‐vendor relationships are examined in a sector of the electronics industry where the manufacturing process is sensitive to the performance of vendors in terms of price, quality and delivery. Two similar user companies with different vendor management approaches are considered and the effects these have on vendor performance and the subsequent results for aspects of the companies' performance examined. Vendors supplying both companies were interviewed on the rationale of their behaviour towards the companie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0
2

Year Published

1987
1987
2002
2002

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 3 publications
1
7
0
2
Order By: Relevance
“…Firms also experienced lower inventory levels and fewer disruptions in production schedules. Supporting Masson's (1986) research, Cusumano and Takeishi (1991) determined that early involvement of suppliers in the new product development process was associated with lower defect rates during production. Krause et al (1998) also explored supplier development programs based on Hahn et al's (1990) definition: "any systematic organizational effort to create and maintain a network of competent suppliers" (p. 3).…”
Section: Purchasing's Relationship With External Suppliersmentioning
confidence: 98%
See 3 more Smart Citations
“…Firms also experienced lower inventory levels and fewer disruptions in production schedules. Supporting Masson's (1986) research, Cusumano and Takeishi (1991) determined that early involvement of suppliers in the new product development process was associated with lower defect rates during production. Krause et al (1998) also explored supplier development programs based on Hahn et al's (1990) definition: "any systematic organizational effort to create and maintain a network of competent suppliers" (p. 3).…”
Section: Purchasing's Relationship With External Suppliersmentioning
confidence: 98%
“…Monczka and Trent (1991) concluded that supplier dependency on sole suppliers required purchasing to manage suppliers more effectively in the areas of quality, delivery, new technology development, and product design. Masson (1986), in a comparative case study of two Scottish electronics manufacturers, found that regular visits with suppliers helped prevent delivery and quality problems. Firms also experienced lower inventory levels and fewer disruptions in production schedules.…”
Section: Purchasing's Relationship With External Suppliersmentioning
confidence: 99%
See 2 more Smart Citations
“…According to these researchers, involvement activities and behaviors are very extensive, including formal assessments of suppliers (Giunipero, 1990;Watts & Hahn, 1993), supplier education and training (Gait & Dale, 1991;Krause, 1997Krause, , 1999Monczka et al, 1993), assistance in solving performance problems of suppliers, provision of guidelines/procedures to improve supplier performance (Krause & Ellram, 1997), and site visits by buying firms (Krause, 1997(Krause, , 1999Masson, 1986). Buying firms' involvement, for the current study, describes these activities and behaviors identified by previous studies.…”
Section: Buying Firms' Involvementmentioning
confidence: 99%